2002
DOI: 10.1002/1099-0682(200208)2002:8<2147::aid-ejic2147>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Isomerization of Allylic Alcohols: Oxidation State Determines Resistance Against Diene Inhibition

Abstract: The novel complex mer-[RuCl 3 (dmso)(phen)] (1) has been prepared and characterized by X-ray diffraction. The ruthenium center is in a distorted octahedral environment with the three chloride ions coordinated in a mer-fashion and an S-bonded dmso ligand trans to one of the phen nitrogen atoms. Electrochemical experiments show two reversible waves in acetonitrile solution, corresponding to the couples Ru III/II (0.11 V) and Ru IV/III (1.73 V). The analogous Ru II complex cis,cis-[RuCl 2 (dmso) 2 (phen)] (2) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Yet, the most active catalyst precursor thus far for the overall hydration-isomerization reaction, [RuCl 3 (dmso)(phen)], is only moderately active in isomerization of allylic alcohols in the absence of dienes [11]. This prompted us to investigate alternative catalyst precursors with higher intrinsic isomerization activities.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Yet, the most active catalyst precursor thus far for the overall hydration-isomerization reaction, [RuCl 3 (dmso)(phen)], is only moderately active in isomerization of allylic alcohols in the absence of dienes [11]. This prompted us to investigate alternative catalyst precursors with higher intrinsic isomerization activities.…”
Section: Introductionsupporting
confidence: 77%
“…The maximum conversion was obtained with a catalytic system formed by in situ mixing of a ruthenium(III) salt and 2,2 0 -bipyridine (bpy) or 1,10-phenanthroline (phen) [9,10]. A subsequent investigation in our group of possible deactivation routes for this type of catalyst [11] led to the discovery of a significantly improved system [12].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on integrated 1 H signal intensities of free and coordinated dmso as well as those of coordinated pta we concluded that the product was [RuCl2(dmso)2(pta)2] (2). The singlet 31 P signal refers to the phosphanes being in trans position each to the other (Scheme 2). This observation is in agreement with that substitution of chloride in this solvent is not favoured.…”
Section: Reactions Of Cis-[rucl2(dmso)4] With Water-soluble Phosphanesmentioning
confidence: 99%
“…[29 ] In addition, pta has been successfully used for synthesis of anticancer Ru(II)-arene complexes [30] . Strikingly, 1 itself was only scarcely used [31,32] as catalyst in such reactions so its study was also accomplished.…”
Section: Introductionmentioning
confidence: 99%